The mathematic model of grades transfer from one grading scale to other - Lieponienė, Jurgita; Kulvietienė, Regina (Lietuvos matematikos rinkinys, 2011)
The article analyzes the problems of the use of ECTS grading scale, presents the constructed mathematic model of grades transfer from one grading scale to other. This model is made on the ground of the ECTS grading table and converts the marks on the principle of most probable grade equivalent evaluating the rating of a mark within the group of analyzable grades.
Keywords: grading scale; ECTS grading table; empirical probabilistic distribution